1990
DOI: 10.1037/0278-6133.9.5.529
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stress on objectively recorded menopausal hot flushes and on flush report bias.

Abstract: The hot flush (or flash) is the most widely reported menopausal symptom. Anecdotal reports suggest that women experience more hot flushes when stressed. Although stress may actually trigger hot flushes, another possibility is that women under stress may be more aware of the physiological changes associated with flushes and, therefore, more likely to report them. The goal of this study was to test these hypotheses by investigating the association between stress and both objective (i.e., physiologically recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…Menopausal women with sleep-disturbing VMS need to correct VMS-increasing factors like life stressors 30 , cigarette use, sedentary behavior and obesity 40 . If making these lifestyle changes does not improve VMS sufficiently so they wake a fewer number of times than twice a week, I suggest that they need therapy.…”
Section: Summary Of Clinical Perspectives On Progesterone For Symptommentioning
confidence: 99%
“…Menopausal women with sleep-disturbing VMS need to correct VMS-increasing factors like life stressors 30 , cigarette use, sedentary behavior and obesity 40 . If making these lifestyle changes does not improve VMS sufficiently so they wake a fewer number of times than twice a week, I suggest that they need therapy.…”
Section: Summary Of Clinical Perspectives On Progesterone For Symptommentioning
confidence: 99%
“…For example, there is some evidence that hot flushes can occur in response to daily 'hassles' [18] or anxiety [19], and demonstrated that general levels of life stress that are likely to occur around the menopause transition may lower the threshold for triggering a hot flush [10]. Five small-scale studies [20][21][22][23][24] have demonstrated the effectiveness of relaxation training, with paced respiration techniques resulting in at least 50 per cent decreases in objectively measured hot flushes in samples of well women.…”
mentioning
confidence: 99%
“…A number of women were taking alternative remedies for hot flashes. These were equally distributed between the groups and were remedies for which there is no evidence of benefit, including evening primrose oil, 14 soy, 6 starflower oil, 2 multivitamins, 3 and reduced caffeine intake. 1 There were no significant differences in clinical characteristics or outcome measures between the groups at baseline, except for oophorectomy.…”
Section: Participants and Follow Upmentioning
confidence: 99%
“…Swartzman et al 14 have demonstrated that women subjected to stress experience an increased number of flashes over a 24-hour period. The fact that stress potentiates, rather than precipitates, flashes suggests that there is not a direct sympathetic response to stress, but supports the view that the flash mechanism is mediated via a central mechanism and would be consistent with norepinephrine influences on the brain.…”
Section: Introductionmentioning
confidence: 99%